Design And Simulation Of Solar Power Generation On Rooftops Towards Clean Technology - Samsurizal, Samsurizal; Pasra, Nurmiati; Adewijaya, Shidarta Rico (Politeknik Negeri Semarang, 2023)
Various efforts are continuously being encouraged and pursued in order to achieve the clean energy transition program. The clear goal is to reach a renewable energy mix target of 23% by 2025. The use of electrical energy is increasing each year, but the availability of fossil energy as the majority fuel used in power generation is becoming limited. Indonesia, being located near the equator, experiences high solar radiation intensity. This potential can be utilized for harnessing solar energy as a power source. Additionally, the utilization of solar energy as an alternative source is more environmentally friendly as it reduces emissions from fossil fuel-based power generation. In this research, the design and planning of a solar power plant are conducted to create clean and environmentally friendly energy. The technical aspects are discussed and simulated using software. The author utilizes the Helioscope application for analyzing the feasibility of installing a solar power plant and conducting simulations. Based on the research results, by utilizing a roof area of 13,725 m2 and installing 2,305 solar modules with a capacity of 550 Wp per module, the solar power plant's capacity amounts to 1,267.8 kWp. The performance ratio is calculated to be 80.6%, and the energy production over a year is estimated at 1,695,000 MW.